The Effect Of Risk Management, Schedule Performance, And Cost Efficiency On The Feasibility Of Infrastructure Project Investment - Hengki Jayeng Pambudi (Eduvest - Journal of Universal Studies, 2025)
Infrastructure project investments tend to face challenges related to risk, schedule delays, and cost efficiency, which can affect the project's financial feasibility. This issue is crucial because appropriate investment decisions are crucial to project success and returns for stakeholders. This study aims to analyze the influence of risk management, schedule performance, and cost efficiency on the investment feasibility of infrastructure projects. The research method used is quantitative, with a population of individuals with direct experience in infrastructure project management. The sample was selected using purposive sampling with the criteria of a minimum of one to three years of experience on related projects. Data were collected through questionnaires, tested for validity and reliability, then analyzed using multiple regression and the R² value to measure the contribution of independent variables to investment feasibility. The results show that risk management, schedule performance, and cost efficiency simultaneously have a significant effect on the investment feasibility of infrastructure projects. The R² value indicates that the independent variables together are able to explain most of the variation in investment feasibility. These findings emphasize the importance of good risk management, proper schedule monitoring, and cost efficiency to improve investment feasibility. The implications of this study can be used as a reference for project management and stakeholders in making more effective infrastructure investment decisions and reducing the risk of financial loss.